The African Academic Diaspora and African Higher Education - Foulds, Kim; Zeleza, Paul Tiyambe (International Higher Education, 2014)
Because of the focus on the impact of “brain drain,” discussions centered on the African academic diaspora often fail to highlight the expansive and innovative relationships between institutions of higher education across Africa and African academic diaporans. Recent initiatives, specifically the Carnegie African Diaspora Fellowship Program, seek to build on existing and develop new relationships to promote academic exchanges and collaborations to internationalize and strengthen the capacities of African universities.